A CONCEPTUAL FRAMEWORK IDENTIFYING SPONSOR ROLE - Lucht, Andreas (My University, 2017)
The project sponsor has received much attention due to its positive influence on the project success. This paper presents a conceptual project life-cycle related framework to examine the sponsor’s impact on project success through characteristics and activities in dependency of the organisational context of Bosch. The main problem is a shortage of practical concepts and evaluation mechanisms which enable a context dependent success and responsibility evaluation as sponsorship can be fulfilled by an individual or group. A quantitative framework was modelled to evaluate the responsibility and the success influence depending on the organisational context. The framework was tested with ten process owners and the results were confirmed in qualitative sponsor interviews. The study identified four main activity groups: - The sponsor supports the project manager in stakeholder management - The sponsor acts as a mentor the project manager - The sponsor strengthens the project manager’s authority and assists in conflicts - The sponsor is involved in benefits management and project prioritisation The study provides a novel framework for future studies to assess the context dependent sponsor performance. Thus, it is suggested to apply the framework to other organisations and contexts.
Keywords: Samhällsbyggnadsteknik; Civil Engineering